Bimbingan Kelompok Sebagai Upaya Pencegahan Perilaku Bullying Di Sekolah Dasar - Rezi Nur Fitriana (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2025)
This study aims to describe the effectiveness of group guidance services using the sociodrama technique as an effort to prevent bullying among elementary school students. This research employed a qualitative descriptive approach with sixth-grade students as the subjects. Data were collected through observation and student reflection, then analyzed using the Miles and Huberman model. The findings indicate that sociodrama effectively enhances students’ understanding of bullying, fosters empathy through role-playing, and encourages positive social behavior. The mindfulness activity in the initial stage also supported students’ emotional readiness. Thus, sociodrama can be used as a preventive strategy to reduce bullying behavior